Pemetaan Proses Bisnis pada Entrrepreneurial Universities - Lenny Rosita (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
Business process mapping is no longer an option but a necessity for organizations that focus on sustainable growth. Efficient and effective business processes increase work productivity and potentially even reduce costs. This research maps business processes level 0 (function), level 1 (process), and level 2 (sub-process) with a value chain approach and BPMN (Business Process Modeling Notation) 2.0. This study aims to develop a comprehensive business process model by collecting qualitative data, which integrates the 9 (nine) criteria for university accreditation requirements, AUN-QA at institutional level, ISO 9001:2015, and ISO 21001:2018. Business process modeling is carried out through 3 stages namely data collection, analysis, and observation. Data was collected through Focus Group Discussions (FGD), literature studies, and observations which are then analyzed, classified, modeled, and validated horizontally and vertically. There are 14 primary activities and 11 supporting activities in universities, where teaching and learning, research, and community service are the core of the primary process. Business process modeling level 1 which is breakdown into level 2 and so on makes it easier to review the process so that an efficient and effective process model is obtained. The results of the mapping are also useful for preparing organizational structures and mapping KPIs (Key Performance Indicators) that support organizational achievements.